2022
DOI: 10.1002/vetr.1626
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the presence of domestic cat hepadnavirus viraemia in cats with biochemical alterations suggestive of liver disease

Abstract: Background The association between domestic cat hepadnavirus (DCH) infection and feline chronic hepatitis and hepatocellular carcinoma has been suggested. However, studies focused on the association between DCH infection and clinicopathological changes consistent with liver disease in cats are not available. Methods This retrospective investigation included sera obtained from 96 cats that had the serum activity of at least alanine aminotransferase or alkaline phosphatase measured during initial diagnostic work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The three youngest DCH positive cats were all 3 months of age, which is the age when maternal immunity is expected to wane. The greatest proportion of DCH positive cats was in the youngest age group here, consistent with the findings of three studies conducted in Italy [ 7 , 13 , 26 ]. These data show that vertical/perinatal transmission, the most common transmission route for human HBV, is possible for DCH.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The three youngest DCH positive cats were all 3 months of age, which is the age when maternal immunity is expected to wane. The greatest proportion of DCH positive cats was in the youngest age group here, consistent with the findings of three studies conducted in Italy [ 7 , 13 , 26 ]. These data show that vertical/perinatal transmission, the most common transmission route for human HBV, is possible for DCH.…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that DCH is circulating among cats in Hong Kong, with a molecular prevalence of 11.1%, as measured by DCH DNA detection in whole blood. The prevalence in other regions varies widely, with DCH-positive cats apparently uncommon in the USA (0.2%) [ 11 ], Japan (0.78%) [ 12 ], and UK (1.9%) [ 10 ]; whereas virus DNA has been readily detected in cats in Australia (6.5%) [ 6 ], Italy (10.8%; 4.2%) [ 7 , 26 ], Thailand (18.5%) [ 15 ], and Malaysia (12.3%) [ 9 ]. Despite study design differences, it is likely that there are genuine regional differences in DCH prevalence, potentially caused by various transmission dynamics, as with human HBV [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, retrospective investigation showed that only a small proportion of cats with liver diseases was positive for DCH. Furthermore, DCH was not detected in cats with a high likelihood of liver diseases (Scavone et al, 2022). These observations imply that DCH infection has a limited contribution on hepatic diseases in cats.…”
Section: Italymentioning
confidence: 80%
“…DCH has gained priority over other infectious agents in cats due to its frequent detection, despite the presence of prominent feline viruses such as feline immunode ciency virus, feline leukemia virus, feline panleukopenia virus, and feline coronavirus [2][3][4]7]. This has led to a surge in research on DCH since 2018, with many papers focusing on its detection and molecular characterization [2][3][4][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Full Textmentioning
confidence: 99%